Sugar apple fairy tale. Volume 1 - Mikawa, Miri (Yen Press, 2023)
"In a world where fairies are caught and sold to the highest bidder, humans aren't exactly on friendly terms with the fae folk. But friendship is exactly what Anne Halford seeks with Challe, her new fairy bodyguard, though he's not so keen on the idea. As his master, Anne tasks him with escorting her through a particularly dangerous area, but with a reluctant fairy bodyguard eager to escape a life of servitude, she'll have to deal with a lot more than she bargained for"--provided by publisher.